Voltage‐dependent anion channel 2 is involved in in vitro capacitation of boar sperm. (20th October 2017) - Martínez‐Abad, S; Castillo‐Martín, M; Gadani, B; Rodríguez‐Gil, JE; Bonet, S; Yeste, M
Contents: Ion channels play an important role during sperm capacitation allowing the transport through plasma and mitochondrial membranes of specific molecules that are essential for the achievement of this physiologic status. Given that voltage‐dependent anion channel 2 (VDAC2) is present in boar spermatozoa and is known to be involved in calcium transport in somatic cells, this study aimed at determining whether it is implicated in sperm capacitation and the acrosome reaction. With this purpose, boar spermatozoa were capacitated in vitro for 4 hr, and acrosome reaction was induced with progesterone for a further hour, with or without the presence of two VDAC2‐inhibitors (erastin and olesoxime) at two different concentrations (10 and 100 μM). At different time points (0, 120, 240, 270 and 300 min), an aliquot was taken and sperm motility, membrane integrity and lipid disorder were evaluated using computer‐assisted sperm analysis and flow cytometry. The addition of the two inhibitors resulted in opposite effects. While erastin 100 μM reduced the percentage of non‐capacitated spermatozoa, the presence of olesoxime at the same concentration prevented the increase in membrane lipid disorder, which is a feature of sperm capacitation. Such prevention was concomitant with a maintaining effect on sperm membrane integrity evaluated through SYBR14/PI. Our results suggest that VDAC2 is involved in the regulation of sperm capacitation, despite the fact that the mechanisms through which erastin and olesoxime act are different.